Exceptional Performance in Competitive Ski Mountaineering: An Inertial Sensor Case Study - Kayser, Bengt; Mariani, Benoit (Frontiers in Sports and Active Living, 2022)
Organized bi-annually in the Swiss Alps since 1984, the « Patrouille des Glaciers » (PDG) is one of the most challenging long distance ski mountaineering (skimo) team competitions in the world. The race begins in Zermatt (1,616 m) and ends in Verbier (1,520 m), covering a total distance of 53 km with a cumulated 4,386 m of ascent and 4,482 m of descent. About 4,800 athletes take part in this competition, in teams of three. We hereby present the performance analysis of the uphill parts of this race of a member (#1) of the winning team in 2018, setting a new race record at 5 hours and 35 minutes, in comparison with two amateur athletes. The athletes were equipped with a Global Navigation Satellite System (GNSS) antenna, a heart rate monitor and a dedicated multi-sensor inertial measurement unit (IMU) attached to a ski which recorded spatial-temporal gait parameters and transition events. The athletes' GNSS and heart rate data were synchronized with the IMU data. Athlete #1 had a baseline VO2max of 80 ml/min/kg, a maximum heart rate of 205 bpm, weighed 69kg and had a BMI of 21.3 kg/m2. During the race he carried 6kg of gear and kept his heart rate constant around 85% of max. Spatio-temporal parameters analysis highlighted his ability to sustain higher power, higher pace, and thus higher vertical velocity than the other athletes. He made longer steps by gliding longer at each step and performed less kick-turns in shorter time. He spent only a cumulative 5 min and 30 s during skins on and off transitions. Skimo performance thus requires a high aerobic power of which a high fraction can be maintained for a prolonged time. These results lend further support to earlier observations that speed of ascent during endurance skimo competitions is function of body weight and race gear, and vertical energy cost of locomotion, with the latter function of climbing gradient. It is also the first study to provide some reference benchmarks for spatio-temporal parameters of elite and amateur skimo athletes during climbing using real-world data.